Dave the Potter - Hill, Laban Carrick; Collier, Bryan (New York : Little, Brown, 2010)
Presents the life of the nineteenth-century artist from South Carolina known as Dave, a Southern slave who became a renowned potter known for signing his pots with poetry.
Includes bibliographical references.
Caldecott Honor Book, 2011
Keywords: Dave, -- fl. 1834-1864; African American potters -- Biography; African American poets -- Biography; Slaves -- Biography -- South Carolina